Stanhopeinae Mesoamericanae. I - Gerlach, Günter; Dressler, Robert L. (Lankesteriana: International Journal on Orchidology, 2016)
T w o n e w s p e c i e s o f t h e s u b t r i b e S t a n h o p e i n a e t r i b e a r e d e s c r i b e d , i l l u s t r a t e d a n d d i s c u s s e d : Coryanthes kaiseriana, from Costa Rica and Panama, and Paphinia vermiculifera from Panama.